Positive Solutions for Singular Semipositone Fractional Differential Equation Subject to Multipoint Boundary Conditions. (2nd July 2017) - Pu, Rui; Zhang, Xingqiu; Cui, Yujun; Li, Peilong; Wang, Weiwei
Abstract : Existence result together with multiplicity result of positive solutions of higher-order fractional multipoint boundary value problems is given by considering the integrations of height functions on some special bounded sets. The nonlinearity may change its sign and may possess singularities on the time and the space variables at the same time.